2014
DOI: 10.1071/sb14002
|View full text |Cite
|
Sign up to set email alerts
|

A systematic study of Bonnaya section Bonnaya (Linderniaceae)

Abstract: Bonnaya Link & Otto section Bonnaya (Linderniaceae) is revised on the basis of morphological evidence. Eleven species, including the new species B. sanpabloensis, are recognised. Several names are reduced to synonymy or excluded from the genus Bonnaya, and a lectotype is designated for Bonnaya cyanea. A key to the genus is also provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…Sprengel (1825, p. 42) and B. veronicifolia (Retz.) Sprengel (1825, p. 41) (Sivarajan and Mathew 1983, Liang and Wang 2014, Sardesai et al 2019, Shimpale et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sprengel (1825, p. 42) and B. veronicifolia (Retz.) Sprengel (1825, p. 41) (Sivarajan and Mathew 1983, Liang and Wang 2014, Sardesai et al 2019, Shimpale et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The species was found to be closely similar to B. antipoda and B. sanpabloensis . However, a critical study of the collected specimens and survey of the relevant literature (Retzius 1786, Colsmann 1793, Sprengel 1824, Blatter and Hallberg 1918, Philcox 1968, Sivarajan and Mathew 1983, Liang and Wang 2014, Shimpale et al 2019) and herbarium collections (BM, C, K, LD) found no match for the plant. Later, comparing our specimens with Wallich Collection (K), we found that the specimens named Torenia gracilis Benth.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the authors have approached Prof. Jenn-Che Wang, National Taiwan Normal University, Taiwan for his expert opinion and, the specimens were identified as Bonnaya sanpabloensis Y.S. Liang & J.C. Wang, a recently described species from South China, Thailand and Philippines (Liang & Wang, 2014). This species was previously been confused with B. antipoda because of its similarities Bonnaya sanpabloensis (Linderniaceae):…”
Section: Introductionmentioning
confidence: 99%
“…Distribution: Known from southern China, Thailand and the Philippines (Liang & Wang, 2014) and now from Maharashtra, India. Notes: During the present study two different populations were noticed from similar habitats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation